2019
DOI: 10.1162/jocn_a_01387
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Auditory Oddball Responses in Dorsolateral Prefrontal Cortex, Basolateral Amygdala, and Auditory Cortex of Macaque

Abstract: The mismatch negativity (MMN) is an ERP component seen in response to unexpected “novel” stimuli, such as in an auditory oddball task. The MMN is of wide interest and application, but the neural responses that generate it are poorly understood. This is in part due to differences in design and focus between animal and human oddball paradigms. For example, one of the main explanatory models, the “predictive error hypothesis”, posits differences in timing and selectivity between signals carried in auditory and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
5
25
0
Order By: Relevance
“…By contrast, only 1 repetition was enough for the initial auditory-evoked response in the mPFC to drop between >50% and >70%, and a second repetition to reach maximum suppression levels (Fig 6E, in black). Similar suppressive dynamics were reported in the orbitofrontal cortex of anesthetized and awake mice [52], in the dorsolateral PFC of alert macaques [53], as well as in human frontal sources [22].…”
Section: The Neuronal Substrate Of Mmn-like Potentials In the Rat Brainsupporting
confidence: 78%
See 2 more Smart Citations
“…By contrast, only 1 repetition was enough for the initial auditory-evoked response in the mPFC to drop between >50% and >70%, and a second repetition to reach maximum suppression levels (Fig 6E, in black). Similar suppressive dynamics were reported in the orbitofrontal cortex of anesthetized and awake mice [52], in the dorsolateral PFC of alert macaques [53], as well as in human frontal sources [22].…”
Section: The Neuronal Substrate Of Mmn-like Potentials In the Rat Brainsupporting
confidence: 78%
“…This could provide a potential explanation for the lack of significant differences between mismatch responses across mPFC fields, despite been quite distinct from each other. The mismatch responses we recorded at the rat mPFC resembled to those recorded at the mouse orbitofrontal cortex [52] and the macaque dorsolateral PFC [53]. It is possible that non-auditory subcortical nuclei such as the hippocampus or the amygdala could compute PEs and then broadcast that signal all over the PFC for further processing and integration.…”
Section: Subcortical Middle Players Could Relay Pe Signals To the Pfcsupporting
confidence: 52%
See 1 more Smart Citation
“…Epidural electrodes placed over the frontal cortices of awake and freely moving rats [ 40 , 45 ] recorded stronger ERPs to DEV than to CTR or STD. In awake macaques, 1 study using multichannel electrodes placed in the dorsolateral PFC found larger responses to DEV than to STD [ 53 ], while another using ECoG found strong mismatch responses in the PFC to deviant changes within a roving-standard paradigm, but not to repetitions or the many-standards control [ 54 ]. Regarding invasive research in human patients, ECoG studies have consistently proven that, in contrast with the AC, the PFC ceases responding to DEV when its occurrence can be expected [ 34 , 37 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, if an intruder detection paradigm elicited more basolateral amygdala activity during an fMRI scan, and such activity scaled with individual differences in Suspiciousness, should we conclude that the amygdala somehow encodes this trait, or that this region is computing threat? An alternative account is that amygdala activity in this paradigm reflected sensitivity to novelty (e.g., Camalier, Scarim, Mishkin, & Averbeck, 2019), not threat, and that equivalent correlations with Suspiciousness would have emerged in an auditory oddball task. To avoid such difficulties, it may be useful for personality neuroscientists to focus on developing accounts of traits whose neurobiological interface may be simpler (e.g., dopamine's role in generating motivated approach behaviors; Guitart-Masip, Duzel, Dolan, & Dayan, 2014) or more easily described in animal models (e.g., threat-related behavioral inhibition).…”
Section: Leverage the Power Of Dimensional Structural Models Of Pmentioning
confidence: 98%